Pengaruh Psikologis Konsumen Dan Citra Merek Terhadap Keputusan Pembelian Produk Lion Star : (Survei pada konsumen Lion Star di Kota Tasikmalaya) - Siti Jenab Mardiana (CV. Ulil Albab Corp, 2022)
This study aims to determine and analyze the influence of consumer psychology and brand image on purchasing decisions for Lion Star products in Tasikmalaya City. The method used in this research is a quantitative approach with a survey method. The population in this study amounted to 100 respondents. The type of data used in this study is primary data obtained from questionnaires. The data analysis used is the classical assumption test and multiple regression analysis using SPSS version 25. The results of this study indicate that consumer psychology and brand image simultaneously have a significant effect on purchasing decisions for Lion Star products in Tasikmalaya City. Consumer Psychology partially has a significant effect on the decision to buy Lion Star products in the City of Tasikmalaya. Brand Image partially has a significant effect on purchasing decisions for Lion Star products in Tasikmalaya City.